Dynamics of Strategy for Planning and Development in the North-East - Planning Commission (Planning Commission, 1986)
The North-Eastern region comprises the five States of Assam, Manipur, Meghalaya, Nagaland and Tripura and the two Union Territories of Arunachal Pradesh and Mizoram. The region accounts for 2.55 lakh square kilometers or 7.7% of the country's total land area and has a population of 266 lakhs (1981 census) representing 3.88 % of the country's total population. 70% of the area is hilly and 88 % people live in villages.
Planning Commission